Phenylboronic Acid-Grafted Chitosan Nanocapsules for Effective Delivery and Controllable Release of Natural Antioxidants: Olive Oil and Hydroxytyrosol - Omnia M. Hendawy; Mohammad M. Al-Sanea; Rehab M. Elbargisy; Hidayat Ur Rahman; Ahmed A. B. Mohamed; Islam Kamal; Reda F. M. Elshaarawy; Amgad I. M. Khedr; Wesam Abd El-Fattah (MDPI AG, 2022)
Olives and virgin olive oil (VOO) are a staple of Mediterranean diets and are rich in several beneficial phenolic compounds, including hydroxytyrosol (HT). Therefore, VOO was extracted from Koroneiki olive fruits, and its volatile as well as phenolic components were identified. Meanwhile, in order to upgrade the pharmaceutical capabilities of VOO and HT, a new conjugate phenylboronic acid-chitosan nanoparticles (PBA-CSNPs, NF-1) was fabricated and applied as nanocapsules for implanting high loading and efficient delivery of VOO and HT nanoformulations (NF-2 and NF-3). Due to the H-bonding interactions and boronate ester formation between the hydroxyl groups of the phenolic content of VOO or HT and the PBA groups in the nanocapsules (NF-1), VOO and HT were successfully loaded into the PBA-CSNPs nanocapsules with high loading contents and encapsulation efficacies. The NF-2 and NF-3 nanoformulations demonstrated physicochemical stability, as revealed by their respective zeta potential values, and pH-triggered drug release characteristics. The in vitro studies demonstrated that the nascent nanocapsules were almost completely nontoxic to both healthy and cancer cells, whereas VOO-loaded (NF-2) and HT-loaded nanocapsules (NF-3) showed efficient anti-breast cancer efficiencies. In addition, the antimicrobial and antioxidant potentials of VOO and HT were significantly improved after nanoencapsulation.